2022
DOI: 10.3390/ijerph19137848
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Campaign among the Health Workers of Fondazione Policlinico Universitario Agostino Gemelli IRCCS: A Cost–Benefit Analysis

Abstract: Vaccinations generate health, economic and social benefits in both vaccinated and unvaccinated populations. The aim of this study was to conduct a cost–benefit analysis to estimate the costs and benefits associated with the COVID-19 vaccination campaign for health workers in Fondazione Policlinico Universitario Agostino Gemelli IRCCS (FPG). The analysis included 5152 healthcare workers who voluntarily received the Pfizer–BioNTech COVID-19 vaccine, divided into physicians, nurses and other health workers. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The basic and vaccination characteristics of the included studies are presented in Table 1. Of the 28 included studies, 13 were from highincome countries (HICs): America (n = 7), [9][10][11][12][13][14][15] Italy (n = 2), 16,17 Canada (n = 1), 18 Denmark (n = 1), 19 the United Kingdom (n = 1), 20 and Spain (n = 1). 21 The remaining studies were from less developed countries, specifically, China (n = 3), [22][23][24] Brazil (n = 2), 25,26 Turkey (n = 1), 27 Iran (n = 1), 28 Pakistan (n = 1), 29 Colombia (n = 1), 30 South Africa (n = 1), 31 Thailand (n = 1), 32 Ukraine (n = 1), 33 Poland (n = 1), 34 Kenya (n = 1), 35 and multiple countries/regions (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic and vaccination characteristics of the included studies are presented in Table 1. Of the 28 included studies, 13 were from highincome countries (HICs): America (n = 7), [9][10][11][12][13][14][15] Italy (n = 2), 16,17 Canada (n = 1), 18 Denmark (n = 1), 19 the United Kingdom (n = 1), 20 and Spain (n = 1). 21 The remaining studies were from less developed countries, specifically, China (n = 3), [22][23][24] Brazil (n = 2), 25,26 Turkey (n = 1), 27 Iran (n = 1), 28 Pakistan (n = 1), 29 Colombia (n = 1), 30 South Africa (n = 1), 31 Thailand (n = 1), 32 Ukraine (n = 1), 33 Poland (n = 1), 34 Kenya (n = 1), 35 and multiple countries/regions (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…36 For the publication years, 15 studies were published in 2021, [11][12][13][14][15][16][18][19][20]22,27,29,[31][32][33] and 13 were published in the first half of 2022. 9,10,17,21,[23][24][25][26]28,30,[34][35][36] Regarding the study perspective, 12 studies were from the health system perspective, 10,12,[16][17][18][19]23,25,26,30,31,33 10 were from the societal or payer perspective, 9,13,15,16,20,24,28,[34][35][36] ...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A previous study of 6649 HCWs in our teaching hospital reported an efficacy of the primary schedule of BNT162b2 against SARS-CoV-2 infection of 91.5% [ 11 ]. Moreover, evidence in the scientific literature shows that providing the Pfizer–BioNTech BNT162b2 mRNA vaccine to HCWs results in significant economic benefits [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the cost-effectiveness of vaccination strategies depends on the vaccine type (Orangi et al 2022;Wang et al 2022) and the booster policy (Mungmunpuntipantip and Wiwanitkit 2022). Given the vaccine's reduced potency and the virus strain variation (Nurchis et al 2022), the economic evaluation of the Covid-19 vaccine needs further analysis for a longer time (Fu et al 2022a).…”
Section: Literature Resultsmentioning
confidence: 99%